Family Mediation in Jordan - Süheyla Akçay Biçen (Darulfunun Ilahiyat)
This article examines how the family reform, mediation, and conciliation offices in Jordan, which were incorporated into law in 2013 and began their activities in 2014, implement family mediation. Although mediation was included in the Civil Code in Jordan in the early 2000s, its application to family law was postponed until a later date. Family mediation was implemented through the family reform, mediation, and conciliation offices established under Sharia courts. Since its implementation, the number of these offices has increased over time, having had a positive impact on the Jordanian society. The family mediation practised here is not limited to divorce mediation but addresses many family-related issues. Moreover, the family mediation model in Jordan, where most population is Muslim, is based on Sharia principles and social realities. In this regard, being a model that meets local and public needs has facilitated the resolution of disputes between families and increased its societal impact. This study aims to provide a model for states that either plan to implement or are currently implementing family mediation, particularly Türkiye, by presenting the family reform, mediation, and conciliation offices in Jordan and their working system.